Time to embrace access programmes for medicines: lessons from the South African flucytosine access programme. (June 2020) - Shroufi, Amir; Govender, Nelesh P.; Meintjes, Graeme; Black, John; Nel, Jeremy; Moosa, Mahomed-Yunus S.; Menezes, Colin; Dawood, Halima; Wilson, Douglas; Duran, Laura Trivino; Ajose, Olawale; Murphy, Richard A.; et al.
Highlights: Market failure has meant that flucytosine, a potentially lifesaving medicine for the treatment of cryptococcal meningitis, is not accessible in African treatment programmes. A recently established access programme has allowed wide scale public sector access to flucytosine in South Africa. We advocate that access programmes for medicines be utilized more widely as part of the solution to addressing market failure. Abstract: Background: Cryptococcal meningitis (CM) is estimated to cause 181 000 deaths annually, with the majority occurring in Sub-Saharan Africa. Flucytosine is recommended by the World Health Organization as part of the treatment for CM. Widespread use of flucytosine could reduce mortality in hospital by as much as 40% compared to the standard of care, yet due to market failure, quality-assured flucytosine remains unregistered and largely inaccessible throughout Africa. Methods: The recently established South African flucytosine clinical access programme is an attempt to address the market failure that led to a lack of public sector access to flucytosine for CM, by making the medicine freely available to tertiary hospitals in South Africa. Results: Between November 2018 and September 2019, 327 CM patients received flucytosine through this programme, with efforts to support sustainable national scale-up presently ongoing. We describe why this programme was needed, its catalytic potential, what is still required to ensure widespread access to flucytosine, and observations from this experience that may have wider relevance. Conclusions: The South African flucytosine access programme illustrates how access programmes may be one part of the solution to addressing the vicious cycle of perceived low demand, limiting manufacturer interest in specific product markets.